HUBUNGAN SIKAP TANGGUNG JAWAB DENGAN KEMAMPUAN PERENCANAAN KARIR SISWA KELAS X JURUSAN AKUNTANSI SMK NEGERI 09 SEMARANG - Farmadhani, Yesica Aurelia (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2023)
Abstract. Research on the Relationship between Attitude of Responsibility and Career Planning Ability of Class X Students majoring in Accounting at SMK Negeri 09 Semarang is motivated by the lack of responsible attitude of Class X students majoring in Accounting, this is indicated by the results of interviews with BK teachers at SMK Negeri 09 Semarang, and Student Needs Questionnaire data (AKPD) that have been found. The formulation of the problem in the subject of this study is to determine the relationship between the attitude of responsibility and the career planning ability of class X students majoring in Accounting at SMK Negeri 09 Semarang?. The purpose of this study was to determine the relationship between the attitude of responsibility and the career planning ability of class X students majoring in Accounting at SMK Negeri 09 Semarang. This type of research is a quantitative research with a correlational research design. The population in this study amounted to 108 students, consisting of class X AKL1, X AKL 2, and X AKL 3. The sampling technique used in this study was saturated sampling technique. The sampling technique in this study used all members of the population owned, namely the samples in this study were class X AKL1, X AKL 2, and X AKL 3. Based on the Pearson product moment correlation test, the r-count correlation value was obtained 0.969. Meanwhile, the r-table value for a sample of 108 with a significance level of 5% is 0.329. Therefore, the r-count value is 0.969 > r-table 0.329. It can be concluded that there is a significant relationship between the attitude of responsibility and the career planning ability of class X students majoring in Accounting at SMK Negeri 09 Semarang. This relationship shows a positive relationship, because the r-count value obtained is positive. This positive relationship means that if the attitude of responsibility is higher then the ability to plan career is lower, and vice versa if the responsibility is lower then the ability to plan career is high. Keywords: Attitude of Responsibility, Ability to Career Planning